Remoção de fluoreto em carvão produzido com borra de café ativada quimicamente com lixívia de cinzas de eucalipto - Bergamini, Mário Henrique Lobo (2023)
The objective of this research was to produce a biochar from exhausted coffee grounds and chemically activate it with natural lye from eucalyptus ash to subsequently evaluate the fluoride adsorption process in an aqueous medium. The following were determined: moisture content, ash content and thermal analysis of coffee grounds; solubility, alkalinity and calcium content of eucalyptus ashes. Activated biochar was subjected to elemental composition (CHNS), X-ray diffraction (XRD), Fourier transform infrared (FTIR), scanning electron microscopy (SEM) and energy dispersion spectroscopy (EDS), N2 adsorption and desorption, pH and potential of zero charge (PZC) for characterization. To select the best production condition for activated biochar, a 3² factorial design was performed. Kinetic adsorption studies were fitted to pseudofirst order, pseudo-second order, Elovich and Weber and Moris models. The nature of the process was studied by Langmuir and Freundlich isotherm models. The result of the factorial design indicated as the best scenario the impregnation rate of 5% and the temperature of 650 °C in the carbonization. SEM showed macroporosity. XRD confirmed the amorphous characteristic of cellulosic materials. The following functional groups were identified in coffee grounds and activated biochar: alcohol or phenol, hydroxyl, methyl, methylene, carbonyl, carboxylic acid, ester, chlorogenic acid, ketone, carbonyl, amino, amide and pyranose ring. The pH of the activated biochar was equal to 8.89 and the PZC was 7.17. Preliminary adsorption tests showed that the best dosage of activated biochar was equal to 3.2 g/L and the concentration of adsorbate caused a decrease in resistance to mass transfer due to the fact that there were more active sites of activated biochar in the liquid medium. However, the removal efficiency decreased with increasing adsorbate concentration. It was observed that coffee grounds, when used as an adsorbent, promoted a small reduction in the adsorbate concentration, with an average removal efficiency of 1.35%. The adsorption kinetics revealed that equilibrium is reached around 800 min and that the pseudo-second order model fitted better. The Freundlich model fitted the experimental data with the best quality. Freundlich's constant n allowed inferring that the adsorption is favorable and the isotherm appears to be L-type, with an initial downward curvature, which suggests less availability of active sites when increasing the adsorbent concentration.